STRATEGIES AND INNOVATIONS TO INCREASE FUNDRAISING INCOME AT YATIM MANDIRI FOUNDATION SIDOARJO BRANCH AMID THE COVID-19 PANDEMIC - Sandy Prastyo Pribadi; Muhammad Abidzarrin; Dewi Riza Lisvi Vahlevi (ICO EDUSHA, 2021)
The spread of Covid-19 cases in Indonesia has devastated various sectors of life. Starting from the economy, education, health, social, and many other crucial factors. In addition to having an impact on the national economy, Covid-19 also has an impact on the National Amil Zakat Agency (BAZNAS) regarding innovations in collecting zakat funds. Based on data from the National Amil Zakat Agency (BAZNAS) stated, in December 2019 recipients of zakat from Muzzaki only reached Rp. 21,347,813,515. This amount was obtained from entity zakat amounting to Rp 569,693,965 and individual zakat amounting to Rp 20,778,119,450 Data collection used observation and interview methods. During the Covid-19 pandemic, the Sidoarjo branch of the Yatim Mandiri Foundation developed digital fundraising strategy services such as internal platforms, external platforms, artificial intelligence platforms, and innovation platforms. In addition, in conducting fundraising, Yayasan Yatim Mandiri Sidoarjo Branch applies two fundraising methods, namely direct (direct) fundraising and indirect (indirect) fundraising. The performance for ziscos, in one day visiting the donor's house to educate the public to pay tithe, infaq and alms of at least 10 people. Zakat funds collected at Yatim Mandiri are distributed to poor orphans so that Yatim Mandiri provides a value of blessing that can be multiplied Keywords : Baznas, Covid-19, Fumdreising, yatimmadiri, zisco References Retno Karunia Putri,dkk, Efek Pandemi Covid-19: Dampak Lonjakan Angka Phk Terhadap Penurunan Ekonomi Indonesia. Jurnal Bismak, vol. 1, no. 2 (2021): 71 Nurhidayat, Pendekatan Ekonomi Syariah Dalam Menyelesaikan Masalah Ekonomi Akibat Pandemi Covid-19. Jurnal Pemikiran Dan Pengembangan Perbankan Syariah, vol. 6, no.1 (2020): 18 Syareif Oebaidillah, ‚BAZNAS Lakukan Inovasi Pengumpulan Zakat Di Masa Pandemi Covid19‛, https://mediaindonesia.com/read/detail/320839-baznas-lakukan-inovasi-pengumpulan-zakatdi-masa-pandemi-covid-19,diakses pada 24 November 2021. [1] Fitri Andriani, Strategi Pengumpulan Dana ZISWAF Di Laz Yatim Mandiri Lamongan Dimasa Pandemi Covid-19 Dalam Prespektif Manajemen Strategi. (Skripsi Fakultas Ekonomi Dan Bisnis Islam Program Studi Manejemen Zakat Dan Wakaf Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2021), 1 [1] Abdul Rivai dan Darsono Prawironegoro, manajemen strategis , (Jakarta :mitra wacana media,2014), 6. [1] Abdul Ghafur, Tiga Kunci Fundraising: Sukses Membangun Lembaga Nirlaba, (Jakarta: PT. Gramedia Pustaka Utama, 2018), 83. [1] Iqbal Rafiqi, Strategi Fundraising Zakat Infaq Shadaqah Di LAZIZNU Dan LAZIZMU Kabupaten Pemekasan. (Tesis Pascasarjana Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2019), 24 Atik Abidah, Analisis Strategi Fundraising Terhadap Peningkatan Pengelolaan Zis Pada Lembaga Amil Zakat Kabupaten Ponorogo. Jurnal Kodifikasia, vol. 10, no. 1 (2016), 12